Histoire de la Jamaïque. 1ère partieTT - - Leslie, Charles (17..?-17.. ; de la Jamaïque) (Nourse, 1751)
Traduction de "A new history of Jamaïca from the earliest accounts to the taking of Porto-Bello", Londres, 1740.